Indigenous communities - Kamal, Mesbah; Islam, Zahidul (Dhaka : Asiatic Society of Bangladesh, 2007)
Contributed articles published under the Cultural Survey of Bangladesh Project; translated from Bengali.
Includes bibliographical references and index.
00026332
Keywords: Indigenous peoples -- Bangladesh; Ethnology -- Bangladesh